A comprehensive review and assessment of islanding detection techniques for PV systems - Mohammad Alobaid; Ahmed G. Abo-Khalil (International Journal of Thermofluids, 2023)
Islanding is a critical issue in the safe and reliable operation of photovoltaic (PV) systems. Different methods have been developed for detecting and disconnecting the system from the grid to prevent islanding. This paper comprehensively compares and discusses the different islanding detection methods for PV systems. The methods include frequency shift, voltage shift, rate of change of frequency (ROCOF), phase jump, active and reactive power methods. The comparison and discussion focus on key factors such as reliability, sensitivity, complexity, cost, and compliance with standards. The suitability of each method is evaluated for different applications and system requirements. Future recommendations for research and development are also discussed, including the need for standardized testing procedures and the potential of new technologies like machine learning and artificial intelligence. This paper provides valuable insights for PV system designers and operators in selecting and implementing the most suitable islanding detection method for their applications.